From platform growth to platform scaling: The role of decision rules and network effects over time - Varga, Suzana; Cholakova, Magdalena; Jansen, Justin J.P.; Mom, Tom J.M.; Kok, Guus J.M. (Journal of Business Venturing, 2023)
Although firms increasingly operate with platform-based business models, only a few have been shown to prosper and survive in the long run. While the literature has traditionally focused on platform growth along with facilitating network effects through value creation, our knowledge around platform scaling remained rather limited. Using an inductive theory elaboration approach with a longitudinal case study of a two-sided platform, Takeaway.com, we offer in-depth understanding about how the top management team members used decision rules to navigate emergent opportunities and challenges over time, and to transition from platform growth to platform scaling. We find that the top management team members purposefully and repeatedly use and revise a portfolio of decision rules to cultivate indirect and data network effects, which allows them to initially facilitate the growth of their platform and over time support the transition to scaling the platform. Our findings provide important implications about the distinct nature of platform growth and platform scaling, and the role of decision rules in cultivating a combination of network effects over time in order to arrive at platform scaling and ensure platform survival and prosperity over an extended period.